Social rights and economics : claims to health care and education in developing countries - Gauri, Varun (2004)
Analyzes rights based and economic approaches to the provision of health care and education in developing countries. Assesses the foundations and uses of social rights in development. Outlines the economic approach to health care and education. Highlights differences and similarities and assess the hard questions that the economic critique poses for rights. Argues that the policy consequences of the approaches overlap considerably.